The lichens of national nature park «Svyaty Gory» (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
69 lichen species of national nature park «Svyaty Gory» are reported. Among them 37 species are new to the park territory, 26 – new to Donetsk chain of hills, 3 – new to the steppe zone of Ukraine and 1 species – new to the Ukrainian plains. Difficulties in identification of doubtful Ascomycota “Lecidea lichenicola” are discussed. Comparative phytogeographical and ecological analysis of the lichens are provided.
Keywords: lichens, national nature park «Svyiaty Gory», taxonomy spectr, geoelement, substrat complex.